Liver Lipocalin 2 Expression in Severely Obese Women With Non Alcoholic Fatty Liver Disease - Auguet, T.; Terra, X.; Quintero, Y.; Martínez, S.; Manresa, N.; Porras, J. A.; Aguilar, C.; Orellana-Gavaldà, J. M.; Hernández, M.; Sabench, F.; Lucas, A.; Pellitero, S.; del Castillo, D.; Richart, C. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Lipocalin 2 (LCN2) has been related to obesity, insulin resistance and metabolic disturbance. However, its relation with non alcoholic fatty liver disease (NAFLD) has hardly been studied.We examined LCN2 circulating levels and its protein and gene expression in liver from women with severe obesity and NAFLD. We analyzed the liver histology of 59 white severely obese women (BMI ≥40 Kg/m2): 15 subjects presented normal liver histology or non-significant liver disease (NL), 18 simple steatosis (SS) and 26 non alcoholic steatohepatitis (NASH). We determined the anthropometric and metabolic features of the women. LCN2 levels were determined by an ELISA and liver mRNA expression by real time RT-PCR. We also studied LCN2 expression in HepG2 liver cells under various inflammatory stimuli.Liver LCN2 protein and gene expression were higher in NAFLD than in obese with NL. Liver LCN2 gene expression correlated with SS (r=0.351, p=0.016), and its protein expression correlated with NASH (r=0.705, p=0.003).LCN2 expression was detected in HepG2 cells after the administration of TNFα, IL6, resistin or adiponectin. LCN2 expression was induced by TNFα, IL6 and resistin.Liver LCN2 is related to NAFLD in severely obese women. Up-regulation of LCN2 expression is detected in HepG2 cells after exposure to TNFα, IL6 and resistin. These results suggest that LCN2 expression is induced under liver harmful conditions.
Keywords: adipocytokines; liver; obesity